Book Review of: Refiguring the Postmaternal: Feminist Responses to the Forgetting of Motherhood. Issue 1 (23rd January 2020) - Boyer, Kate
Refiguring the Postmaternal: Feminist Responses to the Forgetting of Motherhood by Maria Fannin and Maud Perrier, Hardback, ISBN: 9780815392057. Kate Boyer reviews Maria Fannin and Maud Perrier' book, Refiguring the Postmaternal: Feminist Responses to the Forgetting of Motherhood (Routledge, 2018).